Analisis Ganti Kerugian Berdasarkan Perspektif Hukum Perdata - Muklis Muklis (Iuris Studia: Jurnal Kajian Hukum, 2023)
This study analyzes compensation based on a civil law perspective using normative legal research methods by means of library research, namely research on written documents as data sourced from secondary data including primary legal materials, secondary legal materials and tertiary legal materials. The results of the research show that compensation based on a civil law perspective can arise not only due to a breach of performance, but also due to an act against the law. Although according to Article 1243 of the Civil Code, the notion of civil compensation focuses more on compensation for non-fulfillment of an agreement. Compensation based on a civil law perspective can arise either due to a default or unlawful act. The form of compensation is based on the form of loss experienced by the aggrieved party, which can be in the form of material loss or in-material loss.